State Culture: The Advancement of ‘Canadian Values’ Among Immigrants - Wilton, Shauna (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
This article advances the concept of ‘state culture’ as an alternative way of understanding and analyzing the construction and maintenance of nations. State culture refers to the values projected through different state actors and institutions and represented in their policies, practices and literature – it tells us what it means to be part of the political community and what values are central to belonging. Using the concept of state culture as an analytical tool, the article proceeds to explore the contradictions between Canada, as represented by the state, and the claims of sub-national groups through a critical discourse analysis of the materials distributed by the Canadian state to newcomers and potential citizens. Ultimately, this paper reveals the values embedded within these important socialization documents and exposes the myths about the ‘Canadian nation’ contained within them.